The Study on the Most Frequent Internet Application Used and Its Usage in FTM Building - Zaulkffali, Abdullah (2005)
This is a descriptive study and is aimed in obtaining data on the level of internet usage at Faculty of Information Technology Building. The samples of study were the faculty members such as lecturers, administrative staff and students. The field examines includes the most frequent internet application used and what was accessed through the application. This study used exploratory method which involves interviews, questionnaires and monitoring software. The data obtained from interview and questionnaires are used as references in the internet monitoring process which used Internet Access Monitor software. The data recorded by the software is analysed by referring to the number of request of a particular site and also its incoming bandwidth of the 10 top sites. At the end of the study, there were a few suggestion presented in order to improve the internet usage in Faculty of Information Technology building .